Nota sobre a infecção de Lutzomyia evandroi (Diptera: Psychodidae) por Ascocystis chagasi (Adler & Mayrink, 1961) no Estado do Maranhão Infection of Lutzomyia evandroi (Diptera: Psychodidae) by Ascocystis chagasi (Adler & Mayrink, 1961) in the State of Maranhao - Reginaldo Peçanha Brazil; Lee Ryan (Memorias do Instituto Oswaldo Cruz, 1984)
Encontramos a gregarina Ascocystis chagasi, bem como um nematódeo e um tripanosoma nao identificados, em Lutzomyia evandroi da ilha de São Luis, Maranhão. The gregarine Ascocystis chagasi as well as a nematode and an unidentified Trypanosome were found in sandflies of the species Lutzomyia evandroi from the island of São Luis, maranhão State, Brazil.